I am Anything, I am Everything- Ayman Yossri Daydban - Daydban, Ayman Yossri; Kluijver, Robert; Mikdadi, Salwa (Jeddah; Athr Gallery, 2012)
Exhibition catalog
English
Keywords: N4390-5098 Visual Arts. Exhibitions; Saudi Arabia. Palestine